Rubber composition containing scrap rubber
By using a specific proportion of copolymers containing ethylene and 1,3-diene, waste powder, reinforced fillers and crosslinking systems in the rubber composition, the problem of difficult control of the properties of rubber compositions in the prior art is solved, and rubber products with higher performance and durability are achieved, especially suitable for heavy-duty tires.
Patent Information
- Application Number
- CN202180086951.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-22
- Filing Date
- 2021-11-29
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-11-29
AI Technical Summary
The prior art is difficult to apply it to products with higher technical content, especially tires, by better controlling the properties of rubber compositions containing waste powder.
An optimized rubber composition is prepared using at least 50 phr to 100 phr copolymer containing ethylene units and 1,3-diene units, combined with 0.1 to 9 mass% of waste powder, reinforced filler and crosslinking system.
With this composition, the durability and performance of rubber products can be significantly improved, especially under conditions of high mechanical and dynamic stress, suitable for vehicle tires of heavy cargo types.
Smart Images

Figure BDA0004297312950000041 
Figure BDA0004297312950000151 
Figure BDA0004297312950000161
Abstract
Description
Technical Field
[0001] The present invention relates to a rubber composition comprising scrap rubber, in particular to a rubber composition for use in rubber products such as tires. Background Art
[0002] Currently, it is advantageous for manufacturers to be able to reuse products made from recycled rubber in rubber products. Rubber dust is particularly advantageous in this regard, since it is recovered by grinding rubber products. It is often used as a filler in mixtures for the production of parts that are not subject to high mechanical or dynamic stresses.
[0003] However, it would be advantageous to be able to use them in more technologically advanced articles by better controlling the properties of compositions containing them.
[0004] It is known in the prior art that scrap rubber can be used in tires. For example, document WO 2019 / 243711A1 describes the use of certain scrap rubber in tire compositions.
[0005] It is also known that copolymer elastomers containing ethylene units and 1,3-diene units can be used in rubber compositions for tires, as described in WO 2020 / 053521 A1.
[0006] Thus, the applicant has found that a rubber composition having excellent durability can be obtained by using a specific amount of scrap rubber and a specific elastomer in combination. Summary of the invention
[0007] The present invention relates to a rubber composition, which is based on at least 50 to 100 phr of a copolymer containing ethylene units and 1,3-diene units, wherein the ethylene units account for more than 50 mol% of the monomer units of the copolymer; 0.1 to 9 mass % of scrap rubber; a reinforcing filler and a crosslinking system.
[0008] The invention also relates to a rubber article comprising a composition according to the invention, preferably a tyre comprising the composition according to the invention, said tyre preferably comprising said composition in all or part of its tread. In this case, the tyre according to the invention will preferably be chosen from tyres intended to equip two-wheeled vehicles, passenger vehicles, or "heavy-duty" vehicles, i.e. metros, buses, off-road vehicles, heavy road transport vehicles (such as trucks, tractors or trailers), or aircraft, construction equipment, heavy agricultural vehicles or transport vehicles.
[0009] Preferably, the invention relates to a vehicle tyre of the heavy goods type comprising a composition according to the invention, preferably in all or part of its tread.
[0010] I- Components of the Compositions of the Invention
[0011] The rubber composition according to the invention is based on at least one copolymer containing ethylene units and 1,3-diene units, scrap rubber, a reinforcing filler and a crosslinking system.
[0012] The expression "composition based on" is understood to mean that the composition comprises a mixture and / or in situ reaction products of the various essential components used, some of which are able and / or intended to react at least partially with one another during the various stages of manufacturing the composition or during subsequent curing, modification of the initially prepared composition.
[0013] Furthermore, for the purposes of this patent application, for the purpose of preparing the composition before curing, the term "phr" means parts by weight per hundred parts of elastomer. That is, in the case of the presence of scrap rubber, the term "phr" means parts by weight per hundred parts of "new" elastomer, thus removing the elastomer contained in the scrap rubber from the base 100.
[0014] In this specification, unless otherwise expressly stated, all percentages (%) shown are weight percentages. In addition, any numerical interval represented by the expression "between a and b" represents a numerical range extending from greater than a to less than b (i.e., excluding the end values a and b), while any numerical interval represented by the expression "a to b" means a numerical range extending from a to b (i.e., including the strict end values a and b).
[0015] When referring to a "main" compound, for the purposes of the present invention, it is understood to mean that among the compounds of the same type in the composition, this compound is the main one, that is to say the compound which accounts for the largest amount by mass and in particular for more than 50%, preferably for more than 75% of the compounds of the same type. Thus, for example, the main polymer is the composition which accounts for the largest mass relative to the total mass of polymers in the composition. In the same way, the "main" filler is the filler which accounts for the largest weight of the fillers in the composition. For example, in a system comprising only one polymer, said polymer is the main one for the purposes of the present invention, while in a system comprising two polymers, the main polymer accounts for more than half of the mass of the polymers. In contrast, a "minor" compound is a compound which does not account for the largest mass of compounds of the same type.
[0016] For the purposes of the present invention, when referring to the "main" unit (or monomer) within the same compound (or polymer), this is understood to mean that the unit (or monomer) is the main one among the units (or monomers) forming the compound (or polymer), that is, it is the unit (or monomer) that accounts for the largest weight portion among the units (or monomers) forming the compound (or polymer).
[0017] The compounds mentioned in the description may be of fossil origin or may be bio-based. In the case of bio-based, they may be derived partly or entirely from biomass or may be obtained from renewable raw materials derived from biomass. Similarly, the compounds mentioned may also be obtained from the recycling of already used materials, i.e. they may come partly or entirely from a recycling process or from raw materials which themselves come from a recycling process. In particular, polymers, plasticizers, fillers, etc. are concerned.
[0018] I-1 Elastomer
[0019] The elastomers used for the purposes of the present invention are highly saturated diene elastomers, preferably statistical copolymers, comprising ethylene units formed by the polymerization of ethylene. In a known manner, the term "ethylene unit" refers to a -(CH2-CH2)- unit formed by the insertion of ethylene into the elastomer chain. A highly saturated diene elastomer is a copolymer rich in ethylene units, since ethylene units represent at least 50 mol% of all the monomer units of the elastomer.
[0020] Preferably, the highly saturated diene elastomer comprises at least 65 mol% of ethylene units. In other words, ethylene units preferably represent at least 65 mol% of all monomer units of the highly saturated diene elastomer. More preferably, the highly saturated diene elastomer comprises from 65 mol% to 90 mol% of ethylene units, the molar percentages being calculated based on all monomer units of the highly saturated diene elastomer.
[0021] Since the highly saturated diene elastomer is a copolymer of ethylene with a 1,3-diene, it also contains 1,3-diene units formed by the polymerization of 1,3-dienes. In a known manner, the expression “1,3-diene units” means units formed, in the case of isoprene, by insertion of 1,3-diene by 1,4-addition, 1,2-addition or 3,4-addition. 1,3-Diene units are, for example, units of 1,3-dienes containing from 4 to 12 carbon atoms, such as 1,3-butadiene, isoprene, 1,3-pentadiene or aryl-1,3-butadiene. Preferably, the 1,3-diene is 1,3-butadiene, in which case the highly saturated diene elastomer is a copolymer of ethylene with 1,3-butadiene, preferably a statistical copolymer.
[0022] The highly saturated diene elastomers that can be used for the purposes of the present invention can be obtained according to various synthesis methods known to those skilled in the art, depending in particular on the target microstructure of the highly saturated diene elastomer. Generally, it can be obtained by copolymerization of at least one 1,3-diene (preferably 1,3-butadiene) and ethylene according to known synthesis methods, in particular in the presence of a catalytic system comprising a metallocene complex. In this regard, mention may be made of catalytic systems based on metallocene complexes, which are described in EP 1 092 731, WO 2004 / 035639, WO 2007 / 054223 and WO2007 / 054224 in the name of the applicant. Highly saturated diene elastomers (including in the case of random elastomers) can also be obtained by methods using preformed catalytic systems, such as described in WO 2017 / 093654 A1, WO 2018 / 020122 A1 and WO2018 / 020123 A1.
[0023] For the purposes of the present invention, the highly saturated diene elastomer preferably contains units of formula (I) or units of formula (II).
[0024]
[0025] -CH2-CH(CH=CH2)-(II)
[0026] The presence of the saturated 6-membered ring unit (1,2-cyclohexanediyl) of formula (I) in the copolymer is probably due to a very specific series of insertions of ethylene and 1,3-butadiene into the polymer chain during the growth of the polymer chain. When the highly saturated diene elastomer comprises units of formula (I) or units of formula (II), the molar percentages of units of formula (I) and units of formula (II) in the highly saturated diene elastomer (o and p, respectively) preferably satisfy the following formula (Formula 1), more preferably satisfy the formula (Formula 2), and more preferably satisfy the formula (Formula 3), o and p being calculated based on all monomer units of the highly saturated diene elastomer.
[0027] 0 < o+p≤ 35 (Formula 1)
[0028] 0 < o+p ≤ 25 (Formula 2)
[0029] 0 < o+p < 20 (Formula 3)
[0030] The highly saturated diene elastomers that can be used for the purposes of the present invention may consist of a mixture of highly saturated diene elastomers that differ from one another in their microstructure or macrostructure.
[0031] According to the invention, the content of highly saturated diene elastomer in the rubber composition is at least 50 parts by weight per hundred parts of elastomer of the rubber composition (phr). Preferably, the content of highly saturated diene elastomer in the rubber composition varies within the range of 80 to 100 phr. More preferably, it varies within the range of 90 to 100 phr.
[0032] As a further option, if another elastomer is present in the composition, the other elastomer may be chosen from diene elastomers and mixtures thereof. As is known, a "diene" elastomer (or indistinguishable rubber), whether natural or synthetic, means an elastomer which is at least partially (i.e. a homopolymer or copolymer) composed of diene monomer units (monomers with two conjugated or non-conjugated carbon-carbon double bonds). The diene elastomer is preferably chosen from polybutadiene (BR), polyisoprene (which is a synthetic rubber (IR) or natural rubber (NR)), butadiene copolymers, isoprene copolymers and mixtures of these elastomers. Such butadiene copolymers and isoprene copolymers are more preferably butadiene / styrene copolymers (SBR) and isoprene / styrene copolymers (SIR), respectively.
[0033] Determination of the microstructure of elastomers
[0034] when 1 When the resolution of H NMR spectroscopy is not sufficient to assign and quantify all entities, 1 HNMR analysis combined with 13C NMR analysis determines the microstructure of the elastomer. A BRUKER 500MHz NMR spectrometer was used for measurement, with a frequency of 500.43MHz for proton observation and a frequency of 125.83MHz for carbon observation. For insoluble elastomers that can swell in solvents, a 4mm z-stage HRMAS probe was used to perform proton observation and carbon observation in proton decoupling mode. The spectrum was collected at a speed of 4000Hz to 5000Hz. For the measurement of soluble elastomers, a liquid NMR probe was used to perform proton observation and carbon observation in proton decoupling mode. The preparation of insoluble samples was carried out in a rotor filled with analytical materials and a deuterated solvent that can swell, usually deuterated chloroform (CDCl3). The solvent used must always be deuterated, and its chemical properties can be adjusted by a person skilled in the art. The amount of material used can be adjusted to obtain a spectrum with sufficient sensitivity and resolution. The soluble sample is dissolved in a deuterated solvent (about 25 mg of elastomer in 1 ml), which is usually deuterated chloroform (CDCl3). The solvent or solvent blend used must always be deuterated, and its chemical properties can be adjusted by a person skilled in the art. In both cases (soluble sample or swollen sample), the proton NMR uses a 30° single pulse sequence. The spectral window is set so that all resonance lines belonging to the analyzed molecule are observed. The cumulative number is set to obtain a signal-to-noise ratio sufficient to quantify each unit. The cycle delay between each pulse is adjusted to obtain quantitative measurements. Carbon NMR uses a 30° single pulse sequence, with only proton decoupling during the acquisition process to avoid the nuclear Ostwald effect (NOE) and maintain quantification. The spectral window is set so that all resonance lines belonging to the analyzed molecule are observed. The cumulative number is set to obtain a signal-to-noise ratio sufficient to quantify each unit. The cycle delay between each pulse is adjusted to obtain quantitative measurements. NMR measurements are performed at 25°C.
[0035] I-2 Waste rubber
[0036] The composition of the present invention also comprises scrap rubber crumbs (abbreviated as "crumbs" in the remainder of this document).
[0037] Rubber powder is provided in the form of particles, which are optionally converted into the form of rubber sheets. Usually, scrap rubber is produced by grinding or micronizing a cured rubber composition that has been used for the first application (for example in a tire); they are the product of material recovery. Therefore, rubber powder preferably consists of a composition based on at least one elastomer and a filler. Rubber powder is preferably provided in the form of microparticles.
[0038] The term "microparticles" is intended to mean particles whose size (ie their diameter in the case of spherical particles or their largest dimension in the case of anisometric particles) is a few tens or hundreds of micrometers.
[0039] According to the present invention, the amount of scrap rubber in the composition is in the range of 0.1% to 9% by mass (i.e. relative to the total mass of the composition), preferably 0.5% to 7% by mass, more preferably 1% to 6% by mass. In a conventional composition for a tire, these mass contents preferably correspond to a content of about 0.1 to 16 phr. Preferably, the rubber powder content is in the range of 0.5 to 15 phr, preferably 1 to 12 phr, more preferably 1 to 10 phr, and very preferably 2 to 10 phr.
[0040] The scrap rubber has preferably an average size D50 of between 100 μm and 300 μm.
[0041] Moreover, the rubber powder preferably has a particle size distribution satisfying an average size ratio D10 / D50 greater than or equal to 0.5, preferably between 0.55 and 0.95, more preferably between 0.6 and 0.9, and even more preferably between 0.65 and 0.85.
[0042] These specific rubber powders can be obtained by various techniques, in particular by low temperature micronization processes as described in documents US 7 445 170 and US 7 861 958. According to another embodiment of the invention, the rubber powder can be obtained by other micronization processes known to those skilled in the art, not limited to low temperature processes.
[0043] According to the size distribution of the objects obtained, the crumb rubber obtained by the cited process can be subjected to an additional sieving step in order to control this distribution. The sieving can be carried out by various techniques known to those skilled in the art (vibration, centrifugation, suction).
[0044] Likewise, commercially available rubber powders may be used, such as Polydine PD80 rubber powder from Lehigh Technologies.
[0045] As mentioned above, the rubber powder is preferably composed of a composition based on elastomers and fillers. They may also contain all the ingredients usually used in rubber compositions, such as plasticizers, antioxidants, vulcanization additives, etc.
[0046] Thus, the rubber crumb comprises an elastomer, preferably a diene elastomer. This elastomer preferably represents at least 30% by weight, more preferably at least 35% by weight, even more preferably at least 45% by weight of the rubber crumb, the percentages being determined according to standard ASTM E1131. It is preferably chosen from polybutadienes, polyisoprenes (including natural rubber), butadiene copolymers and isoprene copolymers. More preferably, the molar content of units of diene origin (conjugated dienes) present in the diene elastomer is greater than 50%, preferably between 50% and 70%.
[0047] According to a preferred embodiment of the present invention, the rubber powder contains between 5% and 80% by mass, more preferably between 10% and 75% by mass, and very preferably between 15% and 70% by mass of filler.
[0048] The term "filler" is understood in this context to mean any type of filler, whether reinforcing (generally nanoparticles having a weight average size preferably less than 500 nm, in particular between 20 nm and 200 nm) or non-reinforcing or inert (generally microparticles having a weight average size preferably greater than 1 μm, for example between 2 μm and 200 μm). The weight average size of the nanoparticles is measured in a manner known to a person skilled in the art (for example, according to application WO 2009 / 083160, section 1.1). The weight average size of the microparticles can be determined by mechanical sieving.
[0049] As examples of fillers known to those skilled in the art as reinforcing, mention will in particular be made of carbon black or reinforcing inorganic fillers such as silica or alumina in the presence of a coupling agent, or mixtures thereof.
[0050] According to a preferred embodiment of the present invention, the rubber powder contains reinforcing fillers, in particular carbon black or a mixture of carbon blacks as fillers.
[0051] Carbon black or a mixture of carbon blacks preferably accounts for more than 50 mass %, more preferably more than 80 mass %, even more preferably more than 90 mass % of the weight of the reinforcing filler in the rubber powder. According to a more preferred embodiment, the reinforcing filler consists of carbon black or a mixture of carbon blacks.
[0052] Very preferably, the carbon black is present in the rubber powder in an amount ranging from 20% to 40% by mass, more preferably from 25% to 35% by mass.
[0053] Suitable carbon blacks are all carbon blacks, in particular blacks of the HAF, ISAF, SAF, FF, FEF, GPF and SRF type which are conventionally used in rubber compositions for tires (“tire-grade” blacks).
[0054] The rubber powder may contain all other conventional additives added to rubber compositions, in particular rubber compositions for tires. Among these conventional additives, mention may be made of liquid or solid plasticizers, non-reinforcing fillers (such as chalk, kaolin), protective agents, vulcanizing agents. These additives may also be present in the rubber powder in the form of residues or derivatives, since they are able to react during the step of preparing the composition or during the step of crosslinking the composition producing the rubber powder.
[0055] Rubber powder can be a simple rubber material that has been ground / micronized without other treatments. It is also known that these rubber powders can undergo treatments to modify them. Such treatments can include chemical functionalization or desulfurization modifications. It can also be a thermomechanical, thermochemical, biological, etc. treatment. For the present invention, preferably, a rubber powder that has not been subjected to any modification by thermal and / or mechanical and / or biological and / or chemical treatments is used.
[0056] Regarding the components of the rubber powder, for the purpose of the present invention, the rubber powder preferably has an acetone extract between 3% and 30% by mass, more preferably between 3% and 15% by mass, and more preferably between 3% and 10% by mass.
[0057] The rubber powder also preferably has a chloroform extract between 3% and 85% by mass, more preferably between 3% and 20% by mass, and still more preferably between 5% and 15% by mass.
[0058] Preferably, the chloroform extract of the scrap rubber has a mass average molecular weight (Mw) of less than 10000 g / mol, preferably less than 8000 g / mol.
[0059] Preferably, in this type of rubber powder, the ratio of chloroform extract to acetone extract expressed in mass percentage is less than 1.5.
[0060] The characteristics of the scrap rubber dust as described above were measured as follows.
[0061] Measurement of the size of rubber powder particles:
[0062] The particle size mass distribution of the rubber crumb can be measured by laser particle size analyzer on a Mastersizer 3000 device from Malvern. The measurement is carried out by liquid route diluted in alcohol after an ultrasonic pretreatment for 1 minute to ensure particle dispersion. The measurement is carried out according to standard ISO-13320-1 and makes it possible to determine in particular the mean diameter D10 and D50, i.e. the content of particles smaller than this mean diameter, which respectively accounts for 10% and 50% by mass of all particles.
[0063] Measurement of mass fraction of carbon black:
[0064] The carbon black mass fraction is measured by thermogravimetric analysis (TGA) according to standard NF T-46-07, on an instrument of model "TGA / DSC1" from the company Mettler Toledo. About 20 g of sample are introduced into the thermal analyzer and then subjected to a heating program from 25° C. to 600° C. under an inert atmosphere (pyrolyzable phase), followed by a heating program from 400° C. to 750° C. under an oxidizing atmosphere (oxidizable phase). The mass of the sample is measured continuously throughout the heating program. The organic matter content corresponds to the mass loss measured during the pyrolyzable phase relative to the initial mass of the sample. The carbon black content corresponds to the mass loss measured during the oxidizable phase relative to the initial mass of the sample.
[0065] Measurement of acetone extract:
[0066] The acetone extractable content is measured according to standard ISO 1407 by means of a Soxhlet type extractor.
[0067] The sample aliquot (between 500 mg and 5 g) is introduced into the extraction thimble and then placed into the Soxhlet's extractor tube. A volume of acetone equal to two or three times the volume of the extractor tube is placed in the Soxhlet's collector. The Soxhlet is then assembled and then heated for 16 hours.
[0068] The samples were weighed after extraction. The acetone extractable content corresponds to the mass loss of the sample during the extraction process relative to its initial mass.
[0069] It is also possible to calculate the elastomer content, which corresponds to subtracting the content of acetone extractables from the content of organic matter determined by thermogravimetric analysis.
[0070] Measurement of chloroform extract:
[0071] The chloroform extract content is measured according to standard ISO 1407 by means of a Soxhlet type extractor.
[0072] The sample aliquot (between 500 mg and 5 g) is introduced into the extraction thimble and then placed into the Soxhlet's extractor tube. A volume of chloroform equal to two or three times the volume of the extractor tube is placed in the Soxhlet's collector. The Soxhlet is then assembled and then heated for 16 hours.
[0073] The samples were weighed after extraction. The chloroform extract content corresponds to the mass loss of the sample during the extraction process relative to its initial mass.
[0074] Measurement of the average molecular weight of the chloroform extract:
[0075] The molecular mass was determined by size exclusion chromatography according to the molar calibration and according to standard ISO16014.
[0076] The weight average molecular weight (Mw) of the chloroform extract was measured by size exclusion chromatography (SEC) using a refractive index (RI) detector. The system consists of an Alliance 2695 system from Waters, a column oven from Waters, and an RI 410 detector from Waters. A set of columns used consists of two PL GEL MIXED D columns (300x7.5mm 5μm) from Agilent, followed by two PL GEL MIXED E columns (300x7.5mm 3μm). These columns were placed in a column oven thermostated at 35°C. The mobile phase used was non-antioxidant tetrahydrofuran. The flow velocity of the mobile phase was 1ml / min. The RI detector was also thermostated at 35°C.
[0077] The chloroform extract was dried under a nitrogen stream. The dried extract was then dissolved in 250 ppm of non-antioxidant tetrahydrofuran at 1 g / l and stirred for 2 hours. The obtained solution was filtered using a syringe and a disposable 0.45 μm PTFE syringe filter. 100 μl of the filtered solution was injected into the conditioned chromatography system at 1 ml / min at 35°C.
[0078] The Mw result is provided by integrating the chromatographic peaks detected by the RI detector with values exceeding 2000 g / mol. The Mw is calculated by calibration using polystyrene standards.
[0079] I-3 Reinforced Filler
[0080] The rubber composition according to the invention comprises a reinforcing filler, preferably carbon black as a reinforcing filler. The reinforcing filler is usually composed of nanoparticles having an average (mass average) size of less than one micrometer, usually less than 500 nm, usually between 20 nm and 200 nm, particularly preferably between 20 nm and 150 nm.
[0081] Any carbon black, in particular the carbon black conventionally used in tires or their treads (called tire grade carbon black) is suitable as carbon black. Among the carbon blacks, more particularly mention will be made of the reinforcing carbon blacks of the 100, 200 and 300 series, or the carbon blacks of the 500, 600 or 700 series (ASTM grades), such as N115, N134, N234, N326, N330, N339, N347, N375, N550, N683 and N772 carbon blacks. When the rubber composition according to the invention is used for the tread, the carbon black is preferably a carbon black of the 100 or 200 series.
[0082] The content of carbon black can vary over a wide range and is adjusted by those skilled in the art according to the intended use of the rubber composition, particularly in the tire industry. For the use of the rubber composition in treads, particularly vehicle treads intended to carry heavy loads, the content of carbon black in the rubber composition is preferably between 25 phr and 65 phr. For use in the heavy truck industry, the rubber composition may have insufficient reinforcement levels when below 25 phr and may exhibit excessive hysteresis when above 65 phr.
[0083] I-4 Cross-linking system
[0084] In the composition of the invention, use may be made of any type of crosslinking system known to a person skilled in the art for rubber compositions.
[0085] The crosslinking system is preferably a vulcanization system, that is, a vulcanization system based on sulfur (or on a sulfur-donating agent) and a primary vulcanization accelerator. In addition to this basic vulcanization system, various known secondary vulcanization accelerators or vulcanization activators are introduced during the first non-productive stage and / or during the productive stage, such as zinc oxide, stearic acid or equivalent compounds, or guanidine derivatives (especially diphenylguanidine), as described later.
[0086] Sulfur is preferably used in a content of between 0.1 phr and 10 phr, more preferably between 0.2 phr and 5 phr, in particular between 0.3 phr and 3 phr.
[0087] The vulcanization system of the composition according to the invention may also contain one or more other accelerators, such as thiurams, zinc dithiocarbamate derivatives, sulfenamides, guanidines or compounds of the thiophosphate family. Any compound capable of acting as a vulcanization accelerator for diene elastomers in the presence of sulfur may be used in particular, in particular thiazole-type accelerators and derivatives thereof, thiuram-type accelerators or zinc dithiocarbamate-type accelerators. These accelerators are more preferably selected from 2-mercaptobenzothiazole disulfide (abbreviated as "MBTS"), N-cyclohexyl-2-benzothiazole sulfenamide (abbreviated as "CBS"), N,N-dicyclohexyl-2-benzothiazole sulfenamide (abbreviated as "DCBS"), N-(tert-butyl)-2-benzothiazole sulfenamide (abbreviated as "TBBS"), N-(tert-butyl)-2-benzothiazole sulfenimide (abbreviated as "TBSI"), zinc dibenzyl dithiocarbamate (abbreviated as "ZBEC") and mixtures of these compounds. Preferably, sulfenamide type accelerators are used.
[0088] According to a particular embodiment, a mixture of two vulcanization accelerators is used, called primary accelerator and secondary accelerator. Advantageously, the amount of vulcanization accelerator (ie the sum of the amount of primary accelerator and the amount of secondary accelerator) is at least 0.5 phr.
[0089] As primary vulcanization accelerator, use may be made of any compound capable of acting as a vulcanization accelerator for diene elastomers in the presence of sulfur, in particular accelerators of the thiazole type and derivatives thereof, or accelerators of the sulfenamide type. Mention may be made, as examples of primary accelerators, of sulfenamide compounds, such as N-cyclohexyl-2-benzothiazolesulfenamide ("CBS"), N,N-dicyclohexyl-2-benzothiazolesulfenamide ("DCBS"), N-tert-butyl-2-benzothiazolesulfenamide ("TBBS"), and mixtures of these compounds. The primary accelerator is preferably a sulfenamide, more preferably N-cyclohexyl-2-benzothiazolesulfenamide.
[0090] Any compound of thiuram, dithiocarbamate, dithiophosphate, thiourea and xanthate can be used as the secondary vulcanization accelerator. As examples of the secondary accelerator, thiuram disulfide, such as tetraethylthiuram disulfide, tetrabutylthiuram disulfide ("TBTD"), tetrabenzylthiuram disulfide ("TBZTD") and mixtures of these compounds can be mentioned in particular. The secondary accelerator is preferably thiuram disulfide, more preferably tetrabenzylthiuram disulfide.
[0091] Preferably, the vulcanization accelerator is a mixture of sulfenamide and thiuram disulfide. The vulcanization accelerator is advantageously a mixture of N-cyclohexyl-2-benzothiazole sulfenamide and thiuram disulfide, more advantageously a mixture of N-cyclohexyl-2-benzothiazole sulfenamide and tetrabenzylthiuram disulfide.
[0092] Preferably, the mass ratio between the amount of the secondary accelerator and the total amount of the accelerator is less than 0.7. In other words, the mass content or mass amount of the secondary accelerator accounts for less than 70% by mass of the total amount of the accelerator. Preferably, the mass ratio between the amount of the secondary accelerator and the total amount of the accelerator is greater than 0.05, more particularly between 0.05 and 0.7. Preferably, the mass ratio between the amount of the secondary accelerator and the total amount of the accelerator is preferably less than 0.5 and even more preferably less than or equal to 0.3. These preferred ranges make it possible to optimize the compromise between cohesive performance and pressing and curing time by greatly reducing the pressing time while maintaining good limit performance, even in the presence of crack initiation points in the rubber composition.
[0093] According to a preferred embodiment, the mass ratio between the sulfur content and the total amount of accelerators in the rubber composition is less than 1, preferably less than or equal to 0.7, more preferably less than 0.6. Using such a ratio enables obtaining a composition with further improved cohesive properties.
[0094] I-5 Other possible additives
[0095] The rubber composition useful for the purposes of the present invention may also contain all or part of the conventional additives usually used in elastomeric compositions intended for use in tires, such as tire treads. These additives are, for example, fillers (such as silica, alumina), processing agents, plasticizers (such as plasticizing oils or resins), anti-fatigue agents, reinforcing resins, methylene acceptors (such as novolac resins) or methylene donors (such as HMT or H3M), pigments, or protective agents (such as anti-ozonation waxes, chemical antiozonants and antioxidants).
[0096] Of course, the composition according to the invention can be used alone or in the form of a blend, ie a mixture, with any other rubber composition that can be used for manufacturing rubber articles, according to a preferred embodiment, tyres.
[0097] It goes without saying that the invention relates to the rubber compositions described previously in both the "uncured" or non-crosslinked state (ie before curing) and the "cured" or crosslinked or vulcanized state (ie after crosslinking or vulcanization).
[0098] II-Method for preparing the rubber composition
[0099] The rubber composition can be prepared in a suitable mixer according to general procedures well known to those skilled in the art using two consecutive preparation stages: a first stage of thermomechanical processing or kneading at high temperature (up to a maximum temperature between 110° C. and 190° C., preferably between 130° C. and 180° C.) (sometimes called the “non-productive” stage), followed by a second stage of mechanical processing at a lower temperature, generally below 110° C., for example between 40° C. and 100° C. (sometimes called the “productive” stage), during which the sulfur or sulfur donor and the vulcanization accelerator are incorporated.
[0100] By way of example, the first stage (non-productive) is carried out in a single thermomechanical step, during which all the necessary components, except sulfur and vulcanization accelerators, optional additional processing agents and other various additives are introduced into a suitable mixer, such as a conventional internal mixer. The total kneading time in this non-productive stage is preferably between 1 minute and 15 minutes. After cooling the mixture obtained during the first non-productive stage, sulfur and vulcanization accelerators are then usually incorporated into an external mixer, such as an open mill, at low temperature; then all substances are mixed (productive stage) for a few minutes, for example between 2 minutes and 15 minutes.
[0101] The final composition thus obtained can then be calendered, for example, into the form of a sheet or plate, in particular for laboratory characterization, or extruded to form a rubber profile, for example for use in semi-finished products for the manufacture of tires. These products can then be used to manufacture rubber products, such as tires, according to techniques known to those skilled in the art.
[0102] The crosslinking (or curing) may be carried out in a known manner at a temperature generally between 130° C. and 200° C. and under pressure for a sufficient time which may vary, for example, between 5 minutes and 90 minutes, varying in particular with the curing temperature, the crosslinking system employed, the crosslinking kinetics of the composition under consideration or the dimensions of the article to be manufactured. DETAILED DESCRIPTION
[0103] The following examples are used to illustrate the present invention but are not intended to limit the present invention.
[0104] III - Examples of the implementation of the invention
[0105] III-1. Characterization of rubber composition
[0106] In the examples, the rubber compositions were characterized after curing as follows.
[0107] fatigue:
[0108] The fatigue strength expressed in cycles or relative units (ur) is measured in a known manner according to standards ASTM D4482-85 and ISO 40 6943 at 23° C. on 12 specimens subjected to repeated low-frequency tensile strains up to 75% elongation, using a Monsanto (MFTR) machine until the specimen breaks.
[0109] To facilitate comparison of the results, the results are expressed on a base of 100. Values greater than the value of the control (arbitrarily set to 100) indicate an improved result, i.e. the rubber sample has better fatigue strength.
[0110] Dynamic properties:
[0111] The dynamic properties are measured on a viscoanalyzer (Metravib VA4000) according to standard ASTM D 5992-96, more particularly the hysteresis expressed as tan(δ)max, or the stiffness expressed as G*(50%). The data are recorded on a sample of the vulcanized composition (with a thickness of 4 mm and a cross section of 400 mm) subjected to a simple alternating sinusoidal shear stress at a frequency of 10 Hz under controlled temperature conditions (60°C). 2 The response of a cylindrical test specimen of 100 mm (100 mm) is shown. The strain amplitude is swept from 0.1% to 100% (outward cycle) and then from 100% to 1% (return cycle). The results used here are, on the one hand, the loss factor tan(δ), representing the hysteresis of the composition, and, on the other hand, the stiffness G*(50%) at 50% strain. For the outward cycle, the maximum value of tan(δ) observed is shown, denoted tan(δ)max.
[0112] The results in terms of performance are expressed on a base of 100, i.e., a value of 100 was arbitrarily assigned to the best control in order to calculate and subsequently compare tan(δ)max and G*(50%) for the various solutions tested. For tan(δ)max, lower values represent a decrease in hysteresis performance (i.e., larger tan(δ)max values), while higher values represent better performance. For G*(50%), lower values represent a decrease in stiffness performance (i.e., lower G*(50%) values), while higher values represent better performance.
[0113] III-2 Rubber composition
[0114] The elastomer (EBR) was prepared according to the following procedure: 30 mg of the metallocene [{Me2SiFlu2Nd(μ-BH4)2Li(THF)}2, the symbol Flu represents the fluorenyl group of the formula C13H8] were introduced into the first Steinie bottle in the glove box. The cocatalyst (butyloctyl magnesium pre-dissolved in 300 ml of methylcyclohexane in the second Steinie bottle) was introduced into the first Steinie bottle containing the metallocene in the following proportions: 0.00007 mol / L of metallocene, 0.0004 mol / L of cocatalyst. After 10 minutes of contact at ambient temperature, a catalytic solution was obtained. The catalytic solution was then introduced into a polymerization reactor. The temperature in the reactor was then raised to 80°C. When this temperature was reached, the reaction was started by injecting a gaseous mixture of ethylene and 1,3-butadiene (80 / 20 mol %) into the reactor. The polymerization reaction was carried out at a pressure of 8 bar. The ratio of metallocene and cocatalyst was 0.00007 mol / L and 0.0004 mol / L, respectively. The polymerization reaction was stopped by cooling, degassing the reactor and adding ethanol. An antioxidant was added to the polymer solution. The copolymer was recovered by drying in a vacuum oven.
[0115] The rubber compositions whose formulation details are given in Table 1 were prepared in the following manner:
[0116] The elastomer, the reinforcing filler and the various other ingredients, except the sulfur and the vulcanization accelerator, are introduced continuously into an internal mixer (final filling degree: about 70% by volume) having an initial vessel temperature of about 80° C. The thermomechanical processing (non-productive phase) is then carried out in a step having a total duration of about 3 to 4 minutes until a maximum “discharge” temperature of 165° C. is reached. The mixture thus obtained is recovered and cooled, and the sulfur and the vulcanization accelerator are then introduced into a mixer (homofinisher) at 30° C., mixing everything (productive phase) for a suitable time (for example about ten minutes).
[0117] The composition thus obtained is subsequently calendered in the form of plates (thickness ranging from 2 to 3 mm) or thin sheets of rubber for measuring their physical or mechanical properties, or extruded in the form of tire treads.
[0118] Among the compositions shown in Table 1, only composition C2 complies with the present invention. Compositions T1 to T3, C1 and C3 are comparative tests to illustrate the effect of the present invention. The properties of the compositions are shown in Table 2 below.
[0119] Table 1
[0120]
[0121] (1) NR: Natural rubber
[0122] (2) SBR having 15.5 wt% styrene units, 24% 1,2 units for the butadiene portion, Tg = -65°C
[0123] (3) BR: polybutadiene, CB24 from Lanxess; cis-1,4 is 96%; Tg = -107°C
[0124] (4) EBR: an elastomer containing 79 mol % of ethylene units, 7 mol % of 1,2-cyclohexanediyl units, 8 mol % of 1,2-butadienyl units and 6 mol % of 1,4-butadienyl units, prepared as described above
[0125] (5) Polydine PD 80 powder from Lehigh Technologies
[0126] (6) Carbon black, ASTM grade N234
[0127] (7) N-(1,3-Dimethylbutyl)-N'-phenyl-p-phenylenediamine (Santoflex 6-PPD) from Flexsys
[0128] (8) “Pristerene 4931” stearin from Uniqema
[0129] (9) Industrial grade zinc oxide from Umicore
[0130] (10) N-cyclohexyl-2-phenylthiazole sulfenamide (Santocure CBS from Flexsys)
[0131] (11) Diphenylguanidine (Perkacit DPG from Flexsys)
[0132] (12) Tetrabenzylthiuram disulfide (Perkacit TBZTD from Flexsys);
[0133] Table 2
[0134]
[0135] It is noted that only composition C2 according to the invention unexpectedly shows a very large improvement in its durability (measured by its fatigue strength) while retaining the best stiffness and hysteresis.
Claims
1. A rubber composition based on at least: - 50 to 100 phr of a copolymer containing ethylene units and 1,3-diene units, wherein the ethylene units in the copolymer account for more than 50 mol% of the monomer units of the copolymer. - 0.1 to 9% by mass of scrap rubber, relative to the total mass of the composition, - reinforcing fillers, - Cross-linking system.
2. The composition according to claim 1, wherein The copolymer containing ethylene units and 1,3-diene units includes at least 65 mol % of ethylene units.
3. The composition according to claim 1 or 2, wherein The 1,3-diene is 1,3-butadiene.
4. The composition according to claim 1, wherein The content of the copolymer containing ethylene units and 1,3-diene units in the rubber composition is in the range of 80 to 100 phr.
5. The composition according to claim 1, wherein The scrap rubber has an acetone extractable content between 3% and 30% by mass.
6. The composition according to claim 1, wherein The scrap rubber has a chloroform extractability between 3% and 85% by mass.
7. The composition according to claim 1, wherein The scrap rubber has a ratio of chloroform extract to acetone extract expressed in mass percentage of less than 1.
5.
8. The composition according to claim 1, wherein The scrap rubber has an average size D50 of between 100 μm and 300 μm.
9. The composition according to claim 1, wherein The scrap rubber has a particle size distribution that satisfies an average size ratio D10 / D50 greater than or equal to 0.
5.
10. The composition according to claim 1, wherein The content of the scrap rubber is in the range of 0.5% to 7% by mass.
11. The composition according to claim 1, wherein Reinforcing fillers include carbon black.
12. A rubber product comprising the composition according to claim 1.
13. A tire comprising the rubber composition as defined in any one of claims 1 to 11.
Citation Information
Patent Citations
Catalytic system, process for its preparation and that of an ethylene-conjugated diene copolymer
EP1092731A1
Process and apparatus for manufacturing crumb and powder rubber
US7445170B2
Conical-shaped impact mill
US7861958B2
Ethylene / butadiene copolymers, catalytic system of producing same and production of said polymers
WO2004035639A1
Borohydride metallocene complex of a lanthanide, catalytic system including said complex, polymerisation method using same and ethylene / butadiene copolymer obtained using said method
WO2007054223A2